Hypertension − an update for the dental (sedation) team. (2nd June 2019) - Leader, Ross; Thayer, Tom; Maher, Bridget; Bell, Chris
Abstract : Hypertension is the commonest risk factor contributing to the global burden of disease. Public Health England estimates that, in England, 24% of the population are hypertensive, with 40% possibly undiagnosed. With this in mind, dentists, in particular those undertaking sedation, are in a perfect position to screen for high blood pressure and refer on for further detailed assessment. This paper outlines when a referral to the General Medical Practitioner (GP) should be considered, when sedation should be deferred and how hypertension is diagnosed and managed in primary care based on the National Institute for Health and Care Excellence (NICE)/British Hypertension Society (BHS) guidelines. CPD/Clinical Relevance: The purpose of this article is to update General Dental Practitioners (GDPs), including those who practise IV Midazolam sedation, on how patients who present with suspected hypertension are managed by their GP. Consideration is given to what blood pressures are deemed safe to sedate and what blood pressures should be referred for further assessment, even if considered safe to sedate.